Before I go to sleep - Randall, Ronne; Kerins, Tony (Bath, UK : Parragon, 2008)
At bedtime, a child dreams of saying goodnight to the world.
Keywords: Bedtime -- Juvenile fiction; Dreams -- Juvenile fiction